Sufficient Conditions for the Consistency of Maximum Likelihood Estimation Despite Misspecification of Distribution in Multinomial Discrete Choice Models - Ruud, Paul A. (Econometrica, 1983)
Paul A. Ruud, Sufficient Conditions for the Consistency of Maximum Likelihood Estimation Despite Misspecification of Distribution in Multinomial Discrete Choice Models, Econometrica, Vol. 51, No. 1 (Jan., 1983), pp. 225-228